Pembelajaran PJOK Materi Bola Basket di Masa Pasca Pandemi Covid-19 di SMA Kabupaten Pati - Moh Sabih Ainur Ridlo; Ipang Setiawan (Indonesian Journal for Physical Education and Sport, 2022)
This study uses a quantitative descriptive method with a survey approach. The analysis used is descriptive statistics. The purpose of this study was to determine and describe the planning, implementation and evaluation of learning physical education, sports and basketball material after the COVID-19 pandemic in Pati district high school. Pati, namely the percentage of learning planning carried out by the teacher is included in the "very good" category with the percentage reaching 97.7% of the 11 respondents who filled out a questionnaire with 8 questions with a maximum score of 88 scores, getting a score of 86 scores. The percentage of the implementation of learning carried out by the teacher is included in the "very good" category with the percentage reaching 86.4% of the 11 respondents who filled out a questionnaire with 22 questions with a maximum score of 242 scores, getting a score of 209 scores. The percentage of learning evaluations carried out by teachers is included in the "good" category with the percentage reaching 72.7%. samples and other variables are suggested, so it is hoped that the implementation of learning can be identified widely.